The role of natural products in improving lipid metabolism disorder-induced mitochondrial dysfunction of diabetic kidney disease - Deng, Yingping; Zhu, Han; Xing, Jie; Gao, Junwei; Duan, Jiamin; Liu, Peng; Zhong, Guanghui; Cai, Xudong (Frontiers in Physiology, 2025)
Diabetic Kidney Disease (DKD) is one of the most common microvascular complications of diabetes mellitus and an important cause of end-stage renal disease, with a complex pathogenesis and a lack of effective treatment. Lipid metabolism disorders play a key role in the progression of DKD, mainly by inducing mitochondrial dysfunction which in turn promotes renal injury. In recent years, natural products have shown great promise in improving lipid metabolism and mitochondrial homeostasis by virtue of their advantages of multi-targeting and low toxicity. In this article, we review the mechanism of mitochondrial dysfunction induced by lipid metabolism disorders in DKD, and the intervention strategies of natural products.